Hepatotoxicity risk for positive HIV patients on antiretroviral therapy in National Hospital Guillermo Almenara Irigoyen - De la Cruz, Mayte (2011)
We reviewed the risk factors and indicators of hepatotoxicity in patient medical records from outpatients HIV(+) who received the first highly active antiretroviral therapy (HAART), from 1997 to 2003, in the doctor’s office from the service of Medicine I in the National Hospital Guillermo Almenara Irigoyen (HNGAI). The studied sample was constituted by 313 patients, both genders, 18 to 65 years old, with three and more months after starting antiretroviral therapy. The factors evaluated were: sex, chronic hepatitis B (HBV) or C (HCV), glutamate pyruvate GPT and glutamate oxaloacetate GOT elevated basal transaminase, increase of CD 4+ T-cell count after iniciation of HAART. The results indicate that 54% (169 patients) from the studied sample (313 patients) developed hepatotoxicity demonstrated through: GPT and GOT basal high (14,38% y 15,66%, respectively). For our study, by statistical evaluation, there is not evidence for being a risk factor sex, hepatitis B virus (HBV) and/or hepatitis C virus (HCV) or increase of CD4 + T-cell count at baseline. The prevalence of hepatotoxicity is 53, 99%.